Chemopreventive efficacy of juniper berry oil (Juniperus communis L.) on azoxymethane-induced colon carcinogenesis in rat. (2nd January 2021) - Yaman, Turan; Uyar, Ahmet; Kömüroğlu, Ahmet Ufuk; Keleş, Ömer Faruk; Yener, Zabit
Abstract: The aim of this study was to investigate the chemopreventive effects of juniper berry (JB) oil on azoxymethane (AOM)-induced colon cancer in rats. Thirty-two male Wistar albino rats were allocated into four groups: Control, AOM, AOM + JB, and JB groups. Whereas the control group was fed with standard pellet feed, the AOM and AOM + JB groups were administered of AOM (15 mg/kg body weight) subcutaneously once every 2 weeks for 10 weeks. AOM + JB and JB groups additionally received JB oil (100 µl/kg) orally. At the end of the 16-week experimental period, blood and tissue samples were obtained from the rats following necropsy. The macroscopic findings showed that the application of JB oil significantly decreased adenoma and adenocarcinoma formation both numerically and dimensionally. Immunohistochemically, CEA, COX-2, and Ki-67 immune-expressions decreased, and the immune-expression of caspase-3 increased in AOM + JB treated rats. Additionally, JB oil supplementation ameliorated antioxidant defense systems and lipid peroxidation within the colon tissue of AOM + JB treated rats. These results reveal that the JB oil acted as a chemopreventive dietary agent, inhibiting cell proliferation and COX-2 expression and inducing apoptosis, resulting in a significant reduction in colon tumor formation.